Sustainable pavement: a review on the usage of pavement as a mitigation strategy for UHI - Al-Humairi, S. F. I.; Alias, A. H.; Haron, N. A.; Hassim, S.; Mohd Jakarni, F. (Institute of Physics Publishing, 2021)
Urban Heat Island (UHI) phenomenon is currently affecting many millions of people worldwide. The higher temperatures are experienced in urban areas as compared to the surrounding countryside. The UHI effect has been a great threat to human habitation, and the way to mitigate this problem has been a global concern over decades. Artificial and manmade pavements have been recognised as one of the major origins that deteriorate the thermal environments for living. On the one hand, commonly used pavement materials could lead to a reduced latent heat flux and an increased sensible heat flux to the environment. Following this, there is a series of experiments and numerical analysis that has been conducted by researchers. The selection of pavement type requires an understanding of a local context of an area and characteristics of the pavements. This current study emphasises on reviewing the features, factors and impacts of different type of pavements, as well as determining the suitability of different types of pavements. It is expected that the outcome from this study can assist in further understanding of pavements and its effects on UHI, as well as can ultimately assist in reducing the effect of UHI on human population.